Clinical and epidemiological characteristics and outcome of patients with COVID-19 in Sri Lanka; an observational study - M.M.P.T. Jayasekera; H.M.M. Herath; M.K.P. Pathirage; A. Thushan; G. Karthick; D.J. Bernard; T. Dilrukshi; L.S. Piyarathne; N.B. Senevirathne; S. Bhishman; A.A. Jayawardhana; H.P. Sanjeewa; et al. (Sri Lanka College of Internal Medicine, 2022)
Background: Main objective of this study is to evaluate the clinical and epidemiological characteristics and outcome of patients with COVID-19 admitted to six treatment centres in Sri Lanka. Methods: A descriptive retrospective study was conducted in six treatment centres in the country between March 10, 2020, and May 30, 2020. Results: The study included 431 laboratory confirmed patients with COVID- 19. Their mean age was 37± 13.2 years. Of them, 335 (78.2%) were males. The majority were asymptomatic (243, 56.3%) and of the symptomatic patients, the most common symptom was sore throat (81, 19%), followed by cough (72, 17%), headache (72, 17%), fever (50, 12%), and nasal discharge (36, 8%). Hydroxychloroquine (HCQ) was used as a treatment modality in 248 patients, and they had significantly longer (17.6 days) durations of hospital stay compared to those who were not treated (13.6 days) with HCQ. Conclusions: The majority of patients remained asymptomatic during the course of illness. The most common symptom was sore throat, seen in one fifth of patients, followed by cough, and headache. Our study also showed that patients treated with HCQ had significantly longer durations of hospital stay.